Experimental study on thermal runaway and fire behaviors of large format lithium iron phosphate battery. (25th June 2021) - Liu, Pengjie; Li, Yongqi; Mao, Binbin; Chen, Man; Huang, Zonghou; Wang, Qingsong
Highlights: The thermal runaway and fire behaviors of 243 Ah LiFePO4 /graphite batteries are investigated. The temperature characteristics, voltage, mass loss, heat release rate, total heat release and gas release are quantified. The effects of SOC and flame on the thermal runaway process of individual cell are analyzed. The relationship between TR and fire behaviors is revealed. Abstract: With the increase of large-scale lithium ion batteries (LIBs), the thermal runaway (TR) and fire behaviors are becoming significant issues. In this paper, a series of thermal abuse tests were conducted on 243 Ah LIBs in two conditions using an in situ calorimeter. One is "ignited test (case 1)" and the other is involving in "unignited test (case 2)". The flammable substances were ignited by an igniter at the safety venting (SV) under case 1 and the burning behaviors of LIBs were investigated comprehensively from the aspect of temperature characteristics, voltage, mass loss, heat release rate (HRR), total heat release (THR) and gas release. In case 2, the venting behaviors were characterized and the effects of SOC and flame on the TR process of individual cell have also been investigated. The HRR and THR can reach 88.6 kW and 19530.6 kJ, respectively. A real-scale scenario of 50 m 3 is used to assess the gas toxicity. The CO and HF have larger toxicity than other gases. The results indicate that fire hazards of LIBs increase with the SOC. The characteristic temperature is determined by the inner reactions, and the flaming combustion accelerates the TR progress. The relationship between TR and fire behaviors is revealed from the aspects of electrolyte vaporization, gas generation and venting. It is analyzed that the fast exothermic processes during TR are the main causes that lead to the jet fire. Several proposals are advanced to improve the safety application of LIBs.